2001
DOI: 10.1149/1.1381072
|View full text |Cite
|
Sign up to set email alerts
|

Model Electrochemical Cell Study of Cut-Edge Corrosion Inhibition on Coil-Coated Steel Sheet by Chromate-, Phosphate-, and Calcium-Containing Pigments

Abstract: Corrosion at cut edges is the most important failure mechanism of organic-coated, profiled galvanized steel architectural claddings. Currently, edge corrosion is generally controlled by the addition of strontium chromate in the paint primers; however, there is substantial interest in chromate replacements due to environmental reasons. This work describes an experimental study of inhibition with specific relevance to the cut-edge situation; essentially equivalent to a small galvanic cell between zinc and steel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…In phosphate or chromate containing solutions, a deposition layer composed of phosphates or Cr(III) oxyhydroxides was probably formed on steel substrate, inhibiting the oxygen reduction reaction. 4,18,21,26) However, the KPFM results of this study indicate that the corrosion potential of the steel substrates was not significantly influenced by the anti-corrosive pigments; as such, the pigments themselves appear to act as anodic inhibitors that suppress the dissolution rate of the Al-Zn layer.…”
Section: Potential Distribution At Al-znmentioning
confidence: 61%
See 2 more Smart Citations
“…In phosphate or chromate containing solutions, a deposition layer composed of phosphates or Cr(III) oxyhydroxides was probably formed on steel substrate, inhibiting the oxygen reduction reaction. 4,18,21,26) However, the KPFM results of this study indicate that the corrosion potential of the steel substrates was not significantly influenced by the anti-corrosive pigments; as such, the pigments themselves appear to act as anodic inhibitors that suppress the dissolution rate of the Al-Zn layer.…”
Section: Potential Distribution At Al-znmentioning
confidence: 61%
“…Some researchers have focused on the effect of phosphate pigments on the corrosion resistance of Zn-coated steels. [18][19][20][21][22][23] Simões et al studied the corrosion inhibition mechanism of sodium phosphate (Na 3 PO 4 ) at the cut edges of electrogalvanized steels using scanning vibration electrode technique (SVET) and electrochemical impedance spectroscopy (EIS) in phosphate-containing 0.1 M NaCl solution. They summarized that Zn 3 (PO 4 ) 2 , which was formed by the reaction between phosphate and Zn ions, inhibited the anodic dissolution of Zn; 18,19) however, the protective performance of Zn 3 (PO 4 ) 2 was lower than that of zinc chromate.…”
Section: Effect Of Phosphate and Chromate Pigments On Sacrificial Cormentioning
confidence: 99%
See 1 more Smart Citation
“…13) Zin et al assessed the galvanic reactions between Zn and steel using a model cell of cut edges. 14) They demonstrated that chromate initially acts as an anodic inhibitor for Zn corrosion, and after a few hours, it prevents the cathodic reaction on the steel. Muto et al reported that chromate inhibited the oxygen reduction reaction on the steel substrate, providing the conditions for the Zn layer to act as a sacrificial anode.…”
Section: Electrochemical Roles Of Anti-corrosive Pigments In Sacrificmentioning
confidence: 99%
“…The polymer binder and barrier fillers together contribute to the barrier protection of the metal substrate, while active protection is achieved by incorporation of corrosion inhibitive pigments [4][5][6][7]. Phosphate and polyphosphate inhibitive pigments, which are combined with one or more cations of zinc, calcium, aluminium, lithium, magnesium and strontium [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], are commonly used to replace traditional chromate-containing pigments that are environmentally hazardous and carcinogenic. These phosphate or polyphosphates pigments are assumed to be sparingly soluble in water but release free ions that protect the metal substrate at locations of coating damage by passivating the exposed metal or by otherwise forming a protective, precipitated, salt film.…”
Section: Introductionmentioning
confidence: 99%